Pendampingan Strategi Digital Marketing untuk Meningkatkan Penjualan Produk Semprong Mawar Cemal Cemil Echo di Desa Pomahan - Sumani Sumani; Nanik Setyowati (Social Science Academic, 2025)
Pomahan is one of the villages in Pulung District, Ponorogo Regency, East Java Province which has the potential for various Micro, Small and Medium Enterprises (MSMEs), especially entrepreneurs and home industries. This business has become the livelihood of the people in Pomahan Village, Pulung District, Ponorogo Regency. In Pomahan Village itself there are many Micro, Small and Medium Enterprises (MSMEs) who innovate in opening their businesses but are lacking in maximizing the potential of social media as one of their markets, especially in the "Semprong Mawar Cemal Cemil Echo" MSMEs. These MSMEs in using the brand are also not optimal, even though they have been around for a long time, besides that they also pay less attention to the use of social media to promote their business, so that there are only a few regular customers, and product marketing is not yet widespread. Therefore, the people around Ponorogo City, especially in Pomahan Village, do not have many MSME products and brands that are known by the villagers. Departing from the problems that occurred in Pomahan Village, digital marketing strategy assistance was held to increase sales figures and expand the marketing of MSME products in Pomahan Village as a solution for MSME players who are still having difficulties. This assistance method uses the ABCD (Asset Based Community Development) approach which is carried out door-to-door at each MSME actor's house and is carried out in three stages, namely: 1) the planning stage, 2) the socialization stage, and 3) the implementation stage of the mentoring . The result of this assistance is that MSME actors are assisted in developing their competitiveness by using digital media Instagram and marketplace Shopee as marketing media in order to increase sales figures and expand marketing of the "Semprong Mawar Cemal Cemil Echo" product.